Adaptabilitas Genotipe Gandum Introduksi di Dataran Rendah - Yudiwanti Wahyu; Aditya Permana Samosir; Sri Gajatri Budiarti (Buletin Agrohorti, 2013)
The experiment was conducted to study the adaptability of ten introduced wheat genotypes in Bogor, held at SEAMEO BIOTROP Experimental Field, Tajur, Bogor in March-July 2011. Experiments using Randomized Completely Block Design, single factor and three replications. The factor was genotype consisting of wheat genotypes introduced from India (OASIS / SKAUZ / / 4 * BCN-Var 28, HP 1744, LAJ/MO88, RABE/MO88), Turkey (Basribey, Alibey and Menemen), CIMMYT (G-21, G-18 and H-21), as well as two national varieties (Dewata and Selayar) as a control. The results showed that the varieties significantly affect the overall character except number of tillers and number of productive tillers. Menemen is introduced genotype that showed better or no different performance for almost all the characters than Dewata and Selayar as controls.Key words: Dewata, low altitute, Menemen, Selayar